T3 levels in relation to prognostic factors in breast cancer: a population-based prospective cohort study - Tosovic, Ada (BioMed Central, 2014)
BACKGROUND: The issue of a potential association between thyroid conditions/hormones and breast cancer has been studied extensively during the last decades but the results have been inconclusive and almost no studies have investigated breast cancer aggressiveness. We have previously found a positive association between prospectively measured levels of triiodothyronine (T3) and breast cancer incidence as well as breast cancer mortality. We now investigated prediagnostic T3 levels in relation to specific prognostic factors in breast cancer. METHODS: The Malmö Preventive Project is a population-based prospective cohort including 2185 women in whom T3 levels were measured at baseline. That is, total T3 levels were measured before a potential diagnosis of breast cancer. Mean follow-up was 23.3 years and 149 women in the study population were diagnosed with invasive breast cancer. Tumours were classified according to selected prognostic factors of breast cancer; i.e. grade, tumour size, lymph node metastasis, and hormonal receptor status. T3 was handled both as tertiles and as a continuous variable. A Cox’s proportional hazards analysis yielded hazard ratios with 95% confidence intervals. All analyses were also restricted to postmenopausal women. RESULTS: Overall there was a statistically significant association between T3 and “all” breast cancers. The adjusted Hazard Ratio (HR) in the third tertile, as compared to the first, was (1.61:1.07-2.43). There was a statistically significant positive association between the third T3 tertile and large tumours, i.e. > 20 mm, (3.17:1.20-8.36) and the occurrence of lymph node metastases, (4.53:1.60-12.83). Other prognostic factors positively associated with T3 were negative oestrogen receptor (ER) status, (3.52:1.32-9.41) and negative progesterone receptor (PGR) status, (3.52:1.42-8.75). The analyses of T3 as a continuous variable and analysis restricted to postmenopausal women, confirmed the results but also showed an association with smaller tumours and in postmenopausal women a contemporary association with negative lymph nodes. CONCLUSIONS: This prospective study of serum T3 levels in relation to breast cancer aggressiveness is the first of its kind. We found statistically significant positive associations between higher prediagnostic T3 levels and larger tumours, occurrence of lymph node metastases, and negative ER and PGR status.